Influence of protocol variables on outcomes of the star excursion balance test group (SEBT, mSEBT, YBT-LQ) in healthy individuals: a systematic review - Zając, Bartosz; Olszewski, Maciej; Mika, Anna (Frontiers in Physiology, 2024)
The "SEBT group," which includes the Star Excursion Balance Test (SEBT), its modified version (mSEBT), and the Lower Quarter Y-Balance Test (YBT-LQ), is used to assess the limits of stability. Interestingly, the testing protocol allows users a considerable degree of flexibility, which can affect the obtained results. Therefore, the objective of this systematic review was to analyze the impact of different protocol variants within the "SEBT group" on outcomes.Methods: Data were acquired by searching 4 databases (MEDLINE, ScienceDirect, Wiley, Springer Link) focusing on studies published in English in peer-reviewed journals, empirical in nature, conducted on healthy individuals, and examining the effects of various protocol variants on test outcomes. Study quality was assessed with the NHLBI quality assessment tool for before-after (pre-post) studies with no control group.The calculation method based on the average value of 3 repetitions yields statistically significantly higher results compared to other methods. Allowing unrestricted arm movements during the test results in statistically significantly higher scores compared to the procedure that restricts arm movements. The impact of a warm-up, wearing footwear during testing, and using a dedicated kit remains ambiguous. To obtain reliable results, 4-6 familiarization trials are necessary, though fewer may suffice for athletes experienced in performing the test.This systematic review highlights the significant impact of the calculation method and arm movement restrictions on the outcomes of the "SEBT group". The effects of wearing footwear during testing, warm-up, and using a dedicated test kit remain unclear. The required number of familiarization repetitions may varies depending on biological maturity level of the person being tested. Future research should develop a warm-up protocol tailored to the needs of the "SEBT group", and investigate the impact of heel elevation during testing on outcomes.The protocol for this systematic review was prospectively registered in the OSF Registries